2014
DOI: 10.3945/jn.113.188441
|View full text |Cite
|
Sign up to set email alerts
|

Instant Noodle Intake and Dietary Patterns Are Associated with Distinct Cardiometabolic Risk Factors in Korea

Abstract: The consumption of instant noodles is relatively high in Asian populations. It is unclear whether a higher intake of instant noodles is associated with cardiometabolic risk independent of overall dietary patterns. We therefore investigated the association using the Korean National Health and Nutrition Examination Survey IV 2007-2009, a nationally representative cross-sectional survey of the Korean population with a clustered, multistage, stratified, and rolling sampling design. A total of 10,711 adults (54.5% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 51 publications
(70 reference statements)
3
69
1
8
Order By: Relevance
“…Researchers at Harvard University reported a 68% higher risk of metabolic syndrome among women who consume instant noodles ≥ twice/week [1], but not in men. We found that frequent consumption of instant noodles was associated with increased diastolic blood pressure in women.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Researchers at Harvard University reported a 68% higher risk of metabolic syndrome among women who consume instant noodles ≥ twice/week [1], but not in men. We found that frequent consumption of instant noodles was associated with increased diastolic blood pressure in women.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire listed several potential candidate foods important for cardiometabolic risk in addition to instant noodles (fruits [110], vegetables [110], milk and dairy products [11], high-fat fish [112], high-fat and processed meats [113], sweets and confectionery [114], and carbonated beverages [115]), which was divided into nine frequency categories: barely eat, once/month, 2–3 times/month, 1–2 times/week, 3–4 times/week, 5–6 times/week, once/day, twice/day, and 3 times/day. Those food groups were fruits, vegetables (except Kimchi), milk and dairy products (yogurt/cheese, etc.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations